2015
DOI: 10.1186/s12917-015-0319-7
|View full text |Cite
|
Sign up to set email alerts
|

An association between milk and slime increases biofilm production by bovine Staphylococcus aureus

Abstract: BackgroundStaphylococcus aureus is associated with chronic mastitis in cattle, and disease manifestation is usually refractory to antibiotic therapy. Biofilm production is a key element of S. aureus pathogenesis and may contribute to the treatment failure that is consistently reported by veterinarians. Minas Gerais State is the largest milk-producing state in Brazil, and the characterization of bacterial isolates is an important aspect of disease control for dairy farmers. Here, we investigated the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 44 publications
4
33
3
4
Order By: Relevance
“…In these studies and in our study, the percentage of biofilm producing isolates was high, ranging from 97 % to 100 % positivity. The percentage of biofilm producing isolates in our study was, however, higher than those reported by Vasudevan et al (2003); Fox et al (2005) Marques et al (2013), andFabres-Klein et al (2015) found that 80 %, 81 % and 87 % of isolates produced biofilms, respectively.…”
Section: Biofilm Formationcontrasting
confidence: 83%
See 2 more Smart Citations
“…In these studies and in our study, the percentage of biofilm producing isolates was high, ranging from 97 % to 100 % positivity. The percentage of biofilm producing isolates in our study was, however, higher than those reported by Vasudevan et al (2003); Fox et al (2005) Marques et al (2013), andFabres-Klein et al (2015) found that 80 %, 81 % and 87 % of isolates produced biofilms, respectively.…”
Section: Biofilm Formationcontrasting
confidence: 83%
“…Studies conducted with S. aureus isolated from bovine mastitis in different countries reported the concomitant presence of both genes in most of the S. aureus isolates analysed (Vasudevan et al 2003;Cucarella et al 2004;Szweda et al 2012;Melo et al 2013;Prenafeta et al 2014;Bar-Gal et al 2015;Castelani et al 2015;Fabres-Klein et al 2015). Moreover, other studies (Ciftci et al 2009;Dhanawade et al 2010;Coelho et al 2011;Darwish and Asfour 2013;Marques et al 2013) reported that lower percentages of S. aureus of bovine origin harboured these genes.…”
Section: Biofilm Formationmentioning
confidence: 88%
See 1 more Smart Citation
“…Um biofilme maduro contém estruturas tridimensionais específicas, referidas como torres ou cogumelos, separados por canais cheios de líquido (ATSHAN et al, 2012;CUE et al, 2012 O primeiro relato de biofilme foi feito há mais de 70 anos (ZOBELL,1943), e ainda é uma preocupação na área das industrias, especificamente de alimentos, ambientais e biomédicas (FLINT et al, 1997;SIHORKAR;VYAS, 2001;MAUKONEN et al, 2003;VÁZQUEZ-SÁNCHEZ et al, 2013).…”
Section: Lista De Abreviaturas E Siglasunclassified
“…É de extrema importância higienizar os equipamentos de processamento considerando-se tanto a composição inorgânica dos depósitos como a microflora constitutiva. A formação de biofilmes em industrias de produtos lácteos é predominantemente por substâncias bacterianas poliméricas extracelulares (EPS) nos resíduos de leite (FLINT et al, 1997;MITTELMAN, 1998 …”
Section: Biofilmes Em Laticíniosunclassified